2013
DOI: 10.1155/2013/401274
|View full text |Cite
|
Sign up to set email alerts
|

Does Pro12Ala Polymorphism Enhance the Physiological Role of PPARγ2?

Abstract: Obesity and type 2 diabetes mellitus (T2D) are two major public health problems that have motivated the scientific community to investigate the high contribution of genetic factors to these disorders. The peroxisome proliferator activated by gamma 2 (PPARγ2) plays an important role in the lipid metabolism. Since PPARγ2 is expressed mainly in adipose tissue, a moderate reduction of its activity influences the sensitivity to insulin, diabetes, and other metabolic parameters. The present study aims to contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
(48 reference statements)
1
4
0
Order By: Relevance
“…The idea of this work was built on determining a genetic marker for prediction or early detection of CAD in diabetic patients, and we found that, PPAR-γ Pro12Ala polymorphism (rs1801282) was more frequent in diabetic patients with CAD complications than those with diabetes only, thus PPAR-γ Pro12Ala polymorphism increased the risk of CAD among diabetic patients. Our findings are in agreement with a huge study includes approximately 11500 individuals, from which 3870 are obese and 7625 are diabetic [32]. This study correlated the PPAR-γ Pro12Ala polymorphism with obesity and other factors of metabolic syndrome in diabetic patients with CVD.…”
Section: Discussionsupporting
confidence: 92%
“…The idea of this work was built on determining a genetic marker for prediction or early detection of CAD in diabetic patients, and we found that, PPAR-γ Pro12Ala polymorphism (rs1801282) was more frequent in diabetic patients with CAD complications than those with diabetes only, thus PPAR-γ Pro12Ala polymorphism increased the risk of CAD among diabetic patients. Our findings are in agreement with a huge study includes approximately 11500 individuals, from which 3870 are obese and 7625 are diabetic [32]. This study correlated the PPAR-γ Pro12Ala polymorphism with obesity and other factors of metabolic syndrome in diabetic patients with CVD.…”
Section: Discussionsupporting
confidence: 92%
“…The PPARγ2 Pro12Ala polymorphism has been widely implicated in affecting the risk of obesity (25),although genetic evidence of its effect on obesity is inconsistent. In this study, single locus analysis did not show a signi cant main effect of PPARγ2 Prol2Ala (in genotypic test, or odds ratio analysis) on the risk of obesity in the whole sample population.…”
Section: Discussionmentioning
confidence: 99%
“…Pioglitazone is an insulin-sensitizing drug from the thiazolidinediones family [ 1 ] that strongly activates the transcription factor peroxisome proliferator-activated receptor gamma (PPAR-γ) [ 2 , 3 , 4 , 5 , 6 , 7 ]. Due to its biological effects, pioglitazone is widely used as a type 2 diabetes (T2D) treatment, and several studies have shown that PPAR-γ activation can be directly correlated with insulin sensibilization and the regulation of lipidic metabolism ( Figure 1 ) [ 2 , 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The activation of PPAR-γ by pioglitazone seems to play a role in adipocyte differentiation [ 13 ], apoptosis, and hypertrophy, by increasing adiponectin expression [ 14 ], as well as the control of inflammatory cascades via the reduction of tumor necrosis factor α (TNF-α) [ 2 , 3 , 7 ] and interleukin 6 (IL-6) expression [ 6 , 7 ]. Nevertheless, the biological mechanisms of PPAR-γ activation by pioglitazone remains unestablished.…”
Section: Introductionmentioning
confidence: 99%